Analisis Financial Management Behavior Mahasiswa FEB Penerima KIP-K UPN “Veteran” Jawa Timur - Arif Wicaksono, Tegar Mohamad; Takarini, Nurjanti (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2024)
This study aims to determine the influence of financial knowledge, financial attitude, locus of control, and lifestyle on financial management behavior. The study population was FEB UPN